Refrigeration study for domestic application - Anizan, Wan Ramli (2008)
Refrigeration, cooling, and heating processes are important in a variety of everyday situations, including the air conditioning and heating of buildings, and in a treatment, transportation, and preservation of foods and beverages. Refrigeration also finds large scale industrial application, for example, in the manufacture of ice and the dehydration of gases. This paper gives an understanding of refrigeration study for domestic application. By learning and understanding the basic vapour-compression refrigeration systems, the performance of refrigeration system expected can be determined using refrigerator test rig. The literature study has been conducted by two important parameters in order to analyze performance of the refrigerator. These parameters are pressure and temperature. The literature study is crucial at the location of parameter on the test rig that will be develop. This paper also describes procedure to fabricate the test rig. Then, the refrigerator test rig will test in order to analyse the performance of the refrigerator test rig. The performance of the refrigerator test rig analyse by the using the actual pressure-enthalpy diagram of actual refrigeration cycle and by using the equation. This study may help the audience to analyze the actual performance of the refrigerator performance for domestic application.